The HIPK2/CDC14B-MeCP2 axis enhances the spindle assembly checkpoint block by promoting cyclin B translation - Partscht, Patrick; Simon, Alexander; Chen, Nan-Peng; Erhardt, Sylvia; Schiebel, Elmar (Science advances, 2023)
Mitotic perturbations activate the spindle assembly checkpoint (SAC) that keeps cells in prometaphase with high CDK1 activity. Prolonged mitotic arrest is eventually bypassed by gradual cyclin B decline followed by slippage of cells into G1 without chromosome segregation, a process that promotes cell transformation and drug resistance. Hitherto, the cyclin B1 decay is exclusively defined by mechanisms that involve its proteasomal degradation. Here, we report that hyperphosphorylated HIPK2 kinase accumulates in mitotic cells and phosphorylates the Rett syndrome protein MeCP2 at Ser92, a regulation that is counteracted by CDC14B phosphatase. MeCP2S92 phosphorylation leads to the enhanced translation of cyclin B1, which is important for cells with persistent SAC activation to counteract the proteolytic decline of cyclin B1 and therefore to suspend mitotic slippage. Hence, the HIPK2/CDC14B-MeCP2 axis functions as an enhancer of the SAC-induced mitotic block. Collectively, our study revises the prevailing view of how cells confer a sustainable SAC.
Gesehen am 17.10.2023